Analysis of anti-Streptococcus sanguinis IgY ability to inhibit Streptococcus sanguinis adherence - Suryani Hutomo; Heni Susilowati; Dewi Agustina; Widya Asmara (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Streptococcus sanguinis (S. sanguinis), an oral commensal bacterium, is often implicated in infective endocarditis. Its adherence to the tooth surface is the initial step in dental plaque formation. In addition to the important role of S. sanguinis in systemic disease and antimicrobial resistance, it is necessary to develop methods to control dental plaque formation. Immunoglobulin Y (IgY) has been used to prevent bacterial infection. Purpose: The purpose of this study is to analyze the ability of anti-S. sanguinis IgY antibodies to inhibit S. sanguinis adherence to hydroxyapatite (HA) discs as a model of the tooth surface. Methods: Antibodies were produced by immunizing hens with S. sanguinis suspension. Boosters were given three times following the first injection. An agar gel precipitation test (AGPT) was used to detect the presence of anti-S. sanguinis IgY. A bacterial adherence assay was performed twice to analyze the ability of IgY and the optimal concentration required to inhibit bacterial adherence. Results: The formation of a precipitation line using AGPT confirmed the presence of the antibody. In addition, it was shown that the anti-S. sanguinis IgY antibody could inhibit bacterial adherence to HA. Statistical analysis using One-way ANOVA revealed a significant difference in the optical density (OD) value between the groups (p<0.05). The results of electron microscopy scanning confirmed the quantitative analysis by means of a bacterial adherence test. Conclusion: Anti-S. sanguinis IgY has the ability to inhibit adherence of S. sanguinis to HA discs at an optimal concentration of 30%. The inhibitive effect was stronger in the presence of saliva.